2015
DOI: 10.1186/s12943-015-0293-5
|View full text |Cite
|
Sign up to set email alerts
|

Combination of pan-RAF and MEK inhibitors in NRAS mutant melanoma

Abstract: BackgroundApproximately 20% of melanomas contain a mutation in NRAS. However no direct inhibitor of NRAS is available. One of the main signaling pathways downstream of NRAS is the MAPK pathway. In this study we investigated the possibility of blocking oncogenic signaling of NRAS by inhibiting two signaling points in the MAPK pathway.MethodsFourteen NRAS mutated human melanoma cell lines were treated with a pan-RAF inhibitor (PRi, Amgen Compd A), a MEK inhibitor (MEKi, trametinib) or their combination and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…While in the post-sorafenib era the main goal had been to gain specificity towards mutated BRAF lately some effort has been put towards the development of small molecules directed to both BRAF and CRAF and capable to interfere with isoform hetero-and homo-dimerization thus preventing paradoxical activation of CRAF by BRAF inhibitors (72,(105)(106)(107)(108)(109)(110). While this approach has provided promising results in pre-clinical models, their efficacy and the risk of adverse events will have to be tested in early phase trials (NCT02607813, www.clinicaltrials.gov).…”
Section: Potential For Alternative Combination Therapiesmentioning
confidence: 99%
“…While in the post-sorafenib era the main goal had been to gain specificity towards mutated BRAF lately some effort has been put towards the development of small molecules directed to both BRAF and CRAF and capable to interfere with isoform hetero-and homo-dimerization thus preventing paradoxical activation of CRAF by BRAF inhibitors (72,(105)(106)(107)(108)(109)(110). While this approach has provided promising results in pre-clinical models, their efficacy and the risk of adverse events will have to be tested in early phase trials (NCT02607813, www.clinicaltrials.gov).…”
Section: Potential For Alternative Combination Therapiesmentioning
confidence: 99%
“…Also, in KRAS -mutant tumor cells, unbiased shRNA screening showed that genetic ablation of CRAF enhanced MEK inhibitor response [44,70,45] . And the combination of a pan-RAF inhibitor (PRi, Amgen Compd A) with trametinib showed a synergistic effect on the growth inhibition of NRAS -mutant melanoma cells [71] .…”
Section: Vertical Inhibition Of the Raf-mek-erk Cascadementioning
confidence: 99%
“…In preclinical studies, targeting of MEK and ERK in combination potently suppresses levels of phospho-ERK and induces apoptosis in NRAS mutant cells (Morris et al, 2013; Rebecca et al, 2014). Another approach for vertical pathway inhibition uses combined pan-RAF and MEK inhibition (Atefi et al, 2015). Similarly, single compound, dual RAF/MEK inhibitors are currently investigated for their potential therapeutic activity in RAS mutated malignancies, including melanoma (Wada et al, 2014).…”
Section: Direct Targeting Of Mutant Nrasmentioning
confidence: 99%